Helicobacter spp en un perro con vómito crónico reporte de un caso (2003)
ABSTRACT: This article describes a case of a nine year old female spayed Poodle, that was presented to the clinic because of a three year chronic vomiting and occasional intermittent bloody diarrhea with mucus. It had been treated in several veterinary clinics without improvement. It underwent endoscopy and rectoscopy with a diagnose of active diffuse antral chronic gastritis and Helicobacter felis Like Organisms and in colon Helicobacter felis Like Organisms.